2021
DOI: 10.1002/jmri.28033
|View full text |Cite
|
Sign up to set email alerts
|

The Conversion of MRI Data With Multiple b‐Values into Signature‐Like Pictures to Predict Treatment Response for Rectal Cancer

Abstract: Background: Diffusion weighted imaging (DWI) at multiple b-values has been used to predict the pathological complete response (pCR) to neoadjuvant chemoradiotherapy for locally advanced rectal cancer. Non-Gaussian models fit the signal decay of diffusion by several physical values from different approaches of approximation. Purpose: To develop a deep learning method to analyze DWI data scanned at multiple b-values independent on Gaussian or non-Gaussian models and to apply to a rectal cancer neoadjuvant chemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In general, the critical delineation task is manually performed by experienced oncologists, and the process is quite time‐consuming and tedious 299 . To enhance the efficiency of tumor delineation, various machine learning‐based models and tools have been developed 263,266,268,269,271–276,278–284,300,301 . In a study reported by Lin et al., their machine learning‐assisted delineation tool improved the efficiency by nearly 40% compared to manual delineation 265 .…”
Section: Machine Learning In Multiparametric Mrimentioning
confidence: 99%
“…In general, the critical delineation task is manually performed by experienced oncologists, and the process is quite time‐consuming and tedious 299 . To enhance the efficiency of tumor delineation, various machine learning‐based models and tools have been developed 263,266,268,269,271–276,278–284,300,301 . In a study reported by Lin et al., their machine learning‐assisted delineation tool improved the efficiency by nearly 40% compared to manual delineation 265 .…”
Section: Machine Learning In Multiparametric Mrimentioning
confidence: 99%
“…Most studies (15/29) used two or more sequences to build their predictive models. Five studies used only T2WI sequences to construct the models, and the remaining one used DWI sequences ( 44 ). All studies included image slice thicknesses between 2.00mm and 8.0mm.…”
Section: Resultsmentioning
confidence: 99%
“…The 21 included studies were published between 2018 and 2022. More than half of the studies (11/21) were based on a population from China (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), three from South Korea (45)(46)(47), three from Italy (48-50), two from the USA (51,52), one from Brazil (53), and one from Belgium (54). Two studies were prospective, and all the remaining studies (19/21) had a retrospective design.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Endorectal ultrasound (EUS) affords direct visualization and access for biopsy of rectal cancer and its adjacent lymphadenopathy, which has also been used to predict response to nCRT ( 11 ). MRI may provide exquisite anatomical details on tumor morphology and its association with adjacent structure ( 12 , 13 ). However, these additional imaging modalities are more time-consuming and costly as compared to CT imaging.…”
Section: Introductionmentioning
confidence: 99%